Idiopathic Colonic Varix: Presenting as Lower GI Bleeding in an Elderly Male - Saqeb, Khan Md Nazmus; Basak, Deepankar Kumar; Arfin, Mohammad Shamsul (Bangladesh Critical Care Journal, 2021)
Abstract not available Bangladesh Crit Care J March 2021; 9(1): 62-64